2011
DOI: 10.1186/1471-2105-12-390
|View full text |Cite
|
Sign up to set email alerts
|

Classification of microarrays; synergistic effects between normalization, gene selection and machine learning

Abstract: BackgroundMachine learning is a powerful approach for describing and predicting classes in microarray data. Although several comparative studies have investigated the relative performance of various machine learning methods, these often do not account for the fact that performance (e.g. error rate) is a result of a series of analysis steps of which the most important are data normalization, gene selection and machine learning.ResultsIn this study, we used seven previously published cancer-related microarray da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…For example, one study comparing the performance of eight different classification methods showed that NNET and SVMs in general perform better than the other six methods for predicting outcome in eight different cancer microarray datasets [15]. Several studies confirm our finding of RF inferiority when using cross-validation [17, 18, 40]. Interestingly, a study conducting algorithm comparison on microarray gene expression based drug signatures showed that NNET and R-SVM had the best performance when tested in the most heterogeneous datasets [41].…”
Section: Conclusion and Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…For example, one study comparing the performance of eight different classification methods showed that NNET and SVMs in general perform better than the other six methods for predicting outcome in eight different cancer microarray datasets [15]. Several studies confirm our finding of RF inferiority when using cross-validation [17, 18, 40]. Interestingly, a study conducting algorithm comparison on microarray gene expression based drug signatures showed that NNET and R-SVM had the best performance when tested in the most heterogeneous datasets [41].…”
Section: Conclusion and Discussionmentioning
confidence: 75%
“…However, few studies have systematically compared the predictive performance of such methods using microarray gene expression datasets on breast cancer. In their studies, method comparisons have been done within the same datasets by, for example, 10-fold cross-validation, leave-one-out cross-validation, or hold-out procedures [1418], addressing prediction of relapse within a 5-year period [14, 16, 19], or molecular subtype classification [15]. Furthermore, even fewer studies have compared cross-study validation between classification methods within the field of breast cancer research.…”
Section: Introductionmentioning
confidence: 99%
“…The points on the boundaries are called support vectors, while our optimal separating hyperplane is located in the middle of the margin. Literature suggests SVM classifiers have superior and robust performance in identifying predictive biomarkers in the setting of high-dimensional microarray gene expression data [1418]. To overcome overfitting due to small number of arrays and large number of features, we also performed recursive feature elimination (SVM-RFE) algorithm [19] on the SVM to remove features with smallest ranking criterion, which corresponds to components of the SVM weight vector that are smallest in absolute value.…”
Section: Methodsmentioning
confidence: 99%
“…[24,35,[46][47][48][49][50][51][52][53][54][55] Bio4Energy is led by Stellan Marklund and is funded with 20 million euros by the Swedish government for the initial 5-year period 2010-14. Further constellations at Umeå University that deal with forest feedstock optimization include Formas-financed Strong Research Environments BioImprove (2.5 million euros) and FuncFiber (2.5 million euros), [56][57][58][59][60][61][62][63] the Wallenberg-financed Conifer Genome Consortium (7.5 million euros), and the UPSC Berzelii Centre for Forest Biotechnology (10 million euros) [47,64,65] financed by the Swedish Research councils VR and Vinnova.…”
Section: Bio4energymentioning
confidence: 99%